Retention of talented academic researchers: Evidence from a government intervention. (21st July 2016) - Courty, Pascal; Sim, John
Abstract: The Canada Research Chairs (CRC) Program is designed primarily to retain academic talent in Canadian universities by providing targeted grants to outstanding researchers. Once awarded a chair at her home university, a researcher's compensation increases by 6.3% on average, with a significant decline over CRC tenure. Furthermore, the chance of the researcher changing jobs does not decrease. Although universities report spending more than half of the grant on compensation, only a small portion of the grant can be accounted for as a compensation increase. This demonstrates the difficulty in designing government interventions to have an impact on academic retention. Résumé: Rétention des chercheurs académiques talentueux : résultat d'une intervention gouvernementale . Le programme des Chaires de recherche du Canada (CRC) a été dessiné dans le but premier de retenir le talent académique dans les universités canadiennes en fournissant des octrois ciblés aux chercheurs de première qualité. Une fois une chaire attribuée à son université de base, la rémunération du chercheur augmente de 6.3 % en moyenne, avec un déclin significatif au long de la période de la bourse CRC. De plus, la probabilité que le chercheur change d'emploi ne décroît pas. Même si les université rapportent dépenser plus de la moitié de l'octroi en rémunération, seule une petite portion de l'octroi est attribuée à l'augmentation de la rémunération. Voilà qui démontre la difficulté de dessiner des interventions gouvernementales qui ont un impact sur la rétention des chercheurs.